Constant roll inflationary dynamics with generalized potentials f (R, ?, X) gravity - Keskin, A. I.; Yasar, Mehmet; Kurt, K. (Elsevier, 2025)
In this work, we study early-time inflation within a class of f (R, Phi, X) gravity models under a constant-roll condition. Employing a generalized potential of the form V(Phi)(sigma), we derive expressions for the spectral index n(s), and tensor-to-scalar ratio r, demonstrating that the inflationary dynamics are primarily governed by the parameter sigma and the shape of the potential. At the upper limit of n(s,) we obtain a de Sitter-like phase, while at the lower limit, the model transitions to a quintessence-like phase through an effective oscillating equation of state parameter (EoS). Therefore, under the tuning parameter sigma < 1, the model exhibits a smooth transition from a de Sitter-like phase to a quintessence-like phase via the oscillating EoS parameter. The resulting predictions are consistent with recent observations from the Atacama Cosmology Telescope (ACT), combined with CMB lensing and DESI BAO data.
Keywords: Constant-roll inflation; Scalar fields; f (R, Phi, X) Gravity; High energy